2016
DOI: 10.14716/ijtech.v7i5.3163
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Air Flotation and a Membrane Bioreactor for the Treatment of Palm Oil Mill Effluent

Abstract: The combination of baffled air flotation and a membrane system for the treatment of palm oil mill effluent (POME) was studied. The POME was obtained from a palm oil factory in PTPN I Tanjong Seumantoh, Aceh, Indonesia. Operation variables and conditions, such as the hydraulic retention time and air flow rates, were varied to find the optimum process. The air flotation process is able to reduce the concentration of suspended solids and fats/ oils contained in the wastewater, which increases the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…In the last few years, intensive studies have been reported on the use of MBR for POME treatments [12,40,[56][57][58][59][60]. Principally, the MBR treatment processes constitute membrane-filtration and bio-decomposition of organic substance present in the mixed liquor to form a more innocuous product, such as carbon dioxide (CO 2 ) and water [61]. During the filtration process, the membrane retains the microbial flocs and any particles whose size is greater than the pores diameters within the concentrate and produce filtrate with more inoffensive substances [62].…”
Section: Membrane Bioreactor (Mbr) Application For Pome Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In the last few years, intensive studies have been reported on the use of MBR for POME treatments [12,40,[56][57][58][59][60]. Principally, the MBR treatment processes constitute membrane-filtration and bio-decomposition of organic substance present in the mixed liquor to form a more innocuous product, such as carbon dioxide (CO 2 ) and water [61]. During the filtration process, the membrane retains the microbial flocs and any particles whose size is greater than the pores diameters within the concentrate and produce filtrate with more inoffensive substances [62].…”
Section: Membrane Bioreactor (Mbr) Application For Pome Treatmentmentioning
confidence: 99%
“…The applications of the membrane for filtration process in MBR entail the physical estrangement of the suspensions into concentrates and permeate at a certain range of pressure [61,70]. This implies that a membrane acts as a discerning barrier based on the molecular weight of the constituted substances.…”
Section: Membrane In Mbr Systemmentioning
confidence: 99%
See 3 more Smart Citations